2017
DOI: 10.3389/fpls.2017.00277
|View full text |Cite
|
Sign up to set email alerts
|

An active Mitochondrial Complex II Present in Mature Seeds Contains an Embryo-Specific Iron–Sulfur Subunit Regulated by ABA and bZIP53 and Is Involved in Germination and Seedling Establishment

Abstract: Complex II (succinate dehydrogenase) is an essential mitochondrial enzyme involved in both the tricarboxylic acid cycle and the respiratory chain. In Arabidopsis thaliana, its iron–sulfur subunit (SDH2) is encoded by three genes, one of them (SDH2.3) being specifically expressed during seed maturation in the embryo. Here we show that seed SDH2.3 expression is regulated by abscisic acid (ABA) and we define the promoter region (-114 to +49) possessing all the cis-elements necessary and sufficient for high expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…The bZIP genes bZIP28 , bZIP2 , bZIP53 , and bZIP60 play positive roles in abiotic stress signaling and responses [ 62 , 63 ], as well as growth and development [ 23 , 64 ]. However, little is known about the roles of BnbZIP13 and BnbZIP41 .…”
Section: Discussionmentioning
confidence: 99%
“…The bZIP genes bZIP28 , bZIP2 , bZIP53 , and bZIP60 play positive roles in abiotic stress signaling and responses [ 62 , 63 ], as well as growth and development [ 23 , 64 ]. However, little is known about the roles of BnbZIP13 and BnbZIP41 .…”
Section: Discussionmentioning
confidence: 99%
“…SDH2‐3 is specifically expressed in the embryo during seed development (Elorza et al ., ), and its disruption alone was shown to cause delayed seed germination (Roschzttardtz et al ., ). Recent analysis indicated that SDH2‐3 expression in seed is regulated by ABA, with the promoter region containing three ABA‐responsive elements (Restovic et al ., ). In Solanum lycopersicum (tomato), RNA interference lines of SDH2‐2 showed increased rates of photosynthesis and growth caused by their higher stomatal aperture (Araujo et al ., ), similar to the reported SDH1‐1 / sdh1‐1 plants mentioned above (Fuentes et al ., ).…”
Section: Physiological Roles Of Sdh In Plantsmentioning
confidence: 97%
“…Partial inhibition of SDH by the competitive inhibitor malonate or non‐competitive inhibitor TTFA decrease shoot and root growth rate in Arabidopsis (Jardim‐Messeder et al ., ). SDH inhibitors completely block hypocotyl elongation in the dark and seedling establishment in the light, indicating that complex II plays a role in the acquisition of photosynthetic competence and the transition from heterotrophy to autotrophy (Restovic et al ., ). SDH inhibitors are also widely used worldwide as fungicides to prevent the proliferation of molds in cereal crops.…”
Section: Physiological Roles Of Sdh In Plantsmentioning
confidence: 97%
“…In developing wheat grains, in vitro SnRK1 activity was reported in the embryo and endosperm, which together with low T6P in the embryo may support high in vivo SnRK1 activity for embryo maturation (Martínez-Barajas et al, 2011). The C/S1 bZIP transcription factors, in particular, bZIP53, which is expressed late during seed development, have also been proposed to be involved in storage protein synthesis and seed maturation Alonso et al, 2009;Restovic et al, 2017).…”
Section: Seed Developmentmentioning
confidence: 99%